(untitled) (Bangladesh Journal of Medicine, 2024)
The first two cases of Russell’s viper bite (RV)presented in contemporary period from Chapainwabgonj and Patuakhali districts of Bangladesh in 2013. The unfortunate death of both the cases indicates the severity it can produce and difficulties in its management in resource limited settings. Treatment seeking from traditional healer, sub-district hospital could not provide first dose of AV before referral and delayed arrival to hospital are concerned to be addressed to prevent death from bite by RV in future. Basic preventive measures such as careful while working and walking in the field and unnecessary handling of snake could avoid bite in both the cases. Bangladesh. Bangladesh J Medicine 2024; 35: 204-210